Elastography Study of Hamstring Behaviors during Passive Stretching - Le Sant, Guillaume; Ates, Filiz; Brasseur, Jean-Louis; Nordez, Antoine (PloS one, 2015)
The mechanical properties of hamstring muscles are usually inferred from global passive torque/angle relationships, in combination with adjoining tissues crossing the joint investigated. Shear modulus measurement provides an estimate of changes in muscle-tendon stiffness and passive tension. This study aimed to assess the passive individual behavior of each hamstring muscle in different stretching positions using shear wave elastography. The muscle shear modulus of each hamstring muscle was measured during a standardized slow passive knee extension (PKE, 80% of maximal range of motion) on eighteen healthy male volunteers. Firstly, we assessed the reliability of the measurements. Results were good for semitendinosus (ST, CV: 8.9%-13.4%), semimembranosus (SM, CV: 10.3%-11.2%) and biceps femoris long-head (BF-lh, CV: 8.6%-13.3%), but not for biceps femoris short-head (BF-sh, CV: 20.3%-44.9%). Secondly, we investigated each reliable muscle in three stretch positions: 70°, 90° and 110° of hip flexion. The results showed different values of shear modulus for the same amount of perceived stretch, with the highest measurements in the high-flexed hip situation. Moreover, individual muscles displayed different values, with values increasing or BF-lh, SM and ST, respectively. The inter-subject variability was 35.3% for ST, 27.4% for SM and 30.2% for BF-lh. This study showed that the hip needs to be high-flexed to efficiently tension the hamstrings, and reports a higher muscle-tendon stress tolerance at 110° of hip angle. In addition muscles have different passive behaviors, and future works will clarify if it can be linked with rate of injury.